2020
DOI: 10.1002/anie.202011419
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA G‐Quadruplex in SARS‐CoV‐2: A Promising Therapeutic Target for COVID‐19?

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 has become ag lobal threat. Understanding the underlying mechanisms and developing innovativet reatments are extremely urgent. G-quadruplexes (G4s) are important noncanonical nucleic acid structures with distinct biofunctions. Four putative G4-forming sequences (PQSs) in the SARS-CoV-2 genome were studied. One of them (RG-1), which locates in the coding sequence region of SARS-CoV-2 nucleocapsid phosphoprotein (N), has been verified to form astable RNAG4structure in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
169
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(177 citation statements)
references
References 49 publications
8
169
0
Order By: Relevance
“…Several studies have further started investigating the presence of RNA G-quadruplexes (G4s) in the SARS-CoV-2 genome [73][74][75][76]. Of the many predicted G4s, one G4 located within ORF1a ( position 13385) was shown to bind and to be stabilized by BRACO-19 and TMPyP4, two known G4 binders, suggesting that these compounds might represent good scaffolds for the development of RNA-targeted small-molecule drugs [74].…”
Section: Other Structural Elements In the Sars-cov-2 Genomementioning
confidence: 99%
“…Several studies have further started investigating the presence of RNA G-quadruplexes (G4s) in the SARS-CoV-2 genome [73][74][75][76]. Of the many predicted G4s, one G4 located within ORF1a ( position 13385) was shown to bind and to be stabilized by BRACO-19 and TMPyP4, two known G4 binders, suggesting that these compounds might represent good scaffolds for the development of RNA-targeted small-molecule drugs [74].…”
Section: Other Structural Elements In the Sars-cov-2 Genomementioning
confidence: 99%
“…Nucleic acid recognition often focuses on sequence recognition but for RNA, which folds into complex shapes, its structure provides an opportunity for specific targeting; indeed, it is the structure of the UTR that is conserved for function, rather than sequence. Small molecule libraries have been screened for RNA binding (analogous to protein drug screens) [22][23][24] and agents targeting RNA structures include small molecules that hydrogen bond within the heart of trinucleotide DNA/RNA repeats [25], and planar RNA quadruplex binders [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SARS-type coronaviruses it has also been shown that the highly-conserved SARS Unique Domain (SUD), used to sequestrate pro-apoptotic cellular mRNA sequences, is maintained in its active dimeric form by the interaction with G4 RNA sequences. [11][12][13] As a matter of fact, while SARS-CoV-2 genome is in some extent less prone to arrange in quadruplexes, compared to other viruses such as Zika, 14 four putative G4 sequences have been recently evidenced by Zhao et al 15 In particular the so-called RG-1 sequence, located in the nucleocapsid (N) protein coding region, has been characterized using electronic circular dichroism (ECD). The presence of G4s in infected living cells has also been confirmed, and their stabilization by ligands can induce the downregulation of their expression, impairing the maturation and infectivity of viral proteins hence paving the way to appealing therapeutic strategies.…”
mentioning
confidence: 99%
“…At the same time, the high ECD sensitivity to secondary structure rearrangements allows to achieve a molecular resolution giving access to all the subtle structural factors that may be crucial in driving the possible interactions with external ligands. In this communication we study the RG-1 sequence through a combination of multiple sequence alignment, homology modelling, classical molecular dynamics (MD), and hybrid quantum mechanics/molecular mechanics (QM/MM), in order to disentangle all the structural factors associated to the G4 conformations, also by comparing the Time Dependent Density Functional Theory (TD-DFT) simulated ECD spectrum with the experimental one by Zhao et al 15 The full computational strategy of our multiscale approach can be found in Electronic Supplementary Information (ESI). The structure of RG-1 was predicted from a multiple sequence alignment with three DNA G4s sequences corresponding to experimental structures (PDB codes 2N4Y, 16 6T51, 17 5I2V).…”
mentioning
confidence: 99%
See 1 more Smart Citation